A Minute with Nsort on a 32P NEC Windows Itanium2 Server - Nyberg, Chris; Gray, Jim; Koester, Charles (2004)
In March 2004, the Nsort program was able to sort 34 GB of data (340,000,000 100-byte records) in 58 seconds on a 32 processor Itanium® 2 NEC® Express5800/1320Xd running Microsoft® Windows® Server 2003 Datacenter Edition. This set new records for the MinuteSort benchmark. The data was read from one input file at 1.4 GB/sec. The output file was created and written at 1.2 GB/sec. Both files resided on an NTFS file system on a striped logical volume consisting of 8 Eurologic 14-disc SAN blocs attached by 8 Qlogic 2350 SAN HBAs. The 34 GB data set was read into main memory, sorted, and written to the output file. No temporary (or scratch) files were used. In April 2004 on the same NEC server, Nsort was able to sort a 1 TB file in 33 minutes using 21 Qlogic HBAs and 41 Eurologic SAN blocs. This set a new record in the TeraByte Sort benchmark.